O vibrato no violão: aspectos qualitativos e quantitativos - Matheus Almeida Rodrigues (2014)
The present work has investigated the different vibrato techniques in the acoustic guitar, describing them thoroughly with the help of tools of acoustic analysis, aiming to elucidate important matters regarding its execution, such as the quality of each technique, their applicability, etc. After a review of previous works regarding this theme which took into consideration both historical and acoustic aspects , this research, through several experiments with guitar players, intended to present vibratos typology and compare its different techniques and possibilities. This analysis has focused mainly on four aspects: the rate, the deviation of the fundamental frequency, the regularity and the form of the wave. Using a script written for PRAAT software, an approach based on the extraction of the fundamental frequency (f0) has been implemented and used in the main experiments. A second experiment was also proposed with the objective of comprehending the influence of vibrato technique in the performance of the musical piece Prelúdio 4, composed by Heitor Villa Lobos. In order to do that, three volunteers participated on recordings, playing notes with vibrato in different speeds and positions along the instrument. These recordings were later analyzed and discussed in the light of the literature dedicated to the instrument and the information collected through the bibliographic review. For the analysis of the performance of Villa Loboss piece, each musician performed it twice (once without the use of vibrato and once with the use of the technique), and the variations of time between each execution were compared. There can be concluded that there are several ways of performing the vibrato technique and that each one of them can be used in different situations. It is up to the performer to decide which technique is better for each moment.